BDNF gene Val66Met polymorphisms as a predictor for clinical presentation in schizophrenia – recent findings - Farcas, Adriana; Hindmarch, Charles; Iftene, Felicia (Frontiers in Psychiatry, 2023)
Schizophrenia is a highly heritable, severe psychiatric disorder that involves dysfunctions in thinking, emotions, and behavior, with a profound impact on a person’s ability to function normally in their daily life. Research efforts continue to focus on elucidating possible genetic underlying mechanisms of the disorder. Although the genetic loci identified to date to be significantly associated with schizophrenia risk do not represent disease-causing factors, each one of them could be seen as a possible incremental contributor. Considering the importance of finding new and more efficient pharmacological approaches to target the complex symptomatology of this disorder, in this scoping review, we are focusing on the most recent findings in studies aiming to elucidate the contribution of one of the genetic factors involved – the BDNF gene Val66Met polymorphisms. Here we performed a systematic search in Pubmed, Embase, and Web of Science databases with the search terms: (BDNF gene polymorphism) AND (schizophrenia) for articles published in the last 5 years. To be selected for this review, articles had to report on studies where genotyping for the BDNF Val66Met polymorphism was performed in participants diagnosed with schizophrenia (or schizophrenia spectrum disorders or first-episode psychosis). The search provided 35 results from Pubmed, 134 results from Embase, and 118 results from the Web of Science database. Twenty-two articles were selected to be included in this review, all reporting on studies where an implication of the BDNF Val66Met polymorphisms in the disorder’s pathophysiology was sought to be elucidated. These studies looked at BDNF gene Val66Met polymorphism variants, their interactions with other genes of interest, and different facets of the illness. The Met/Met genotype was found to be associated with higher PANSS positive scores. Furthermore, Met/Met homozygous individuals appear to present with worse cognitive function and lower levels of serum BDNF. In the Val/Val genotype carriers, increased BDNF levels were found to correlate with weight gain under Risperidone treatment. However, due to heterogeneous results, the diversity in study populations and studies’ small sample sizes, generalizations cannot be made. Our findings emphasize the need for further research dedicated to clarifying the role of gene polymorphisms in antipsychotic treatment to enhance specificity and efficacy in the treatment of schizophrenia.